Penuaan Elektrode CuCr1Zr Spot Welding dengan Pendekatan Numerical - Agus Sifa (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2016)
This study is to develop the constitutive equations to describe the mechanical deformation of the surfaces active of electrode. Most of tests are isotherms to characterize the material behavior at each temperature. The results isothermal test are used to identify the parameters of the law by using softwere SiDoLo, it shows the difference affected temperature. We can determine the value of the variable aging is a value between 0-1, the results identification of material aging through numerical calculations show the final result 0.9, then we can say that the specimens have been tested aging